2017
DOI: 10.1038/s41598-017-01733-0
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality analysis of Hyper-reflective Foci and Hard Exudates in Patients with Diabetic Retinopathy

Abstract: To investigate the correlations between hyper-reflective foci and hard exudates in patients with non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) by spectral-domain optical coherence tomography (SD OCT) images. Hyper-reflective foci in retinal SD OCT images were automatically detected by the developed algorithm. Then, the cropped CFP images generated by the semi-automatic registration method were automatically segmented for the hard exudates and corrected by the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…As BCVA generally improved as treatment with ranibizumab progressed, it may be suggested that a reduction of intraretinal hyperreflective foci followed by anti-VEGF therapy may at least partly represent a positive predictive morphological feature in the eyes with DME. This assumption has also been suggested previously [ 18 ], it and is supported by our findings during an observation period of 5 years.…”
Section: Discussionsupporting
confidence: 93%
“…As BCVA generally improved as treatment with ranibizumab progressed, it may be suggested that a reduction of intraretinal hyperreflective foci followed by anti-VEGF therapy may at least partly represent a positive predictive morphological feature in the eyes with DME. This assumption has also been suggested previously [ 18 ], it and is supported by our findings during an observation period of 5 years.…”
Section: Discussionsupporting
confidence: 93%
“…Hyper-reflective foci When monitoring the retina of wet AMD patients using spectral domain optical coherence tomography (SD-OCT), small, dense particles-thereby referred to as hyper-reflective foci (HF)-were identified (Framme et al, 2010;Altay et al, 2016). Similarly, HF were found in eyes of patients with different stages of diabetic retinopathy (De Benedetto et al, 2015;Korot et al, 2016), and a positive correlation between HF number, hard exudate size, disease severity, and inflammation has been recognized (Bolz et al, 2009;Lammer et al, 2014;Niu et al, 2017). Interestingly, the appearance and resolution of HF can be used to complement current diagnostic tools and predict disease progression and therapeutic success (Gallagher et al, 2007;Coscas et al, 2013;Abri Aghdam et al, 2015).…”
Section: Mononuclear Phagocyte-targeted Therapy In Patients With Retimentioning
confidence: 89%
“…Recent studies demonstrated that ROS-TXNIP pathway mediates NLRP3 inflammasome activation in DR conditions in vitro and in vivo in rats. High glucose induces sustained upregulation of TXNIP, ROS generation, and inflammation in a Müller cell line of rats, and antioxidants or TXNIP silencing blocked IL-1b and IL-18 secretion in high-glucose-exposed human retinal microvascular endothelial cells (Devi et al, 2012;Chen et al, 2017). These results provide a potential therapeutic target for the treatment of DR.…”
Section: Triggers Of Inflammasome Activation In the Retinamentioning
confidence: 96%
“…The HRS might be precursors of hard exudates but they can also be seen independently without the formation of hard exudates. 27,28 In previous studies, HRS have shown to be involved in the refractory DMO. 7 Furthermore, as seen in the previous studies, the decrease in the number of HRS seen in this study after dexamethasone treatment suggests that HRS might be inflammatory.…”
Section: Discussionmentioning
confidence: 96%